Mathematics learning and the students' reality in the context of rice farming - Cristina da Silva Martins Paraol; Vandoir Stormowski (Universidade Cruzeiro do Sul, Ensino de Ciências e Matemática, 2022)
The paper presents the planning and implementation of a classroom practice, with the aim of analyzing the articulation of students' reality and the learning process in mathematics. The students' reality considered refers to a municipality in which rice farming predominates and there is also a project to implement an environmental protection park. The study has a qualitative approach, and analyzes the classroom process and the data derived from it. The central theoretical contribution is based on Critical Mathematics Education, both in practice planning and in data analysis. The results indicate the importance of considering the reality of students in the classroom by allowing an attribution of meaning to the mathematical concepts covered, by allowing a reading of reality based on mathematical interpretation, and by allowing reflections on reality by articulating the background and foreground from the students.